Transnational review of visual standards for driving: How Australia compares with the rest of the world. (3rd July 2019) - Yan, Mabel K.; Kumar, Himeesh; Kerr, Nathan; Medeiros, Felipe A.; Sandhu, Sukhpal S.; Crowston, Jonathan; Kong, Yu X. G.
Abstract: Importance: Driving is a highly visual task and a primary mode of transportation for many people around the world. Background: There appears to be little uniformity of vision standards across the world for driving. We reviewed the basic screening visual requirements for obtaining standard private and commercial driving licences for a total of 70 jurisdictions, and reviewed the evidence behind these standards. Design: Systematic review of basic screening vision standards worldwide for driving and literature review. Samples: Published online documentation on visual acuity and field requirements for driving. Methods: Journal articles, government reports and websites obtained via a Google search were used to review the regulations for driving. This was limited by the comprehensiveness of resources, and countries were excluded if the requirements were unclear or unattainable. A literature review was performed using Medline with keywords vision, driving and visual field. Main Outcome Measures: Visual parameters used for driving assessment. Results: The results suggest significant variations across the world. The visual acuity requirements for a private licence range from a minimum of 6/9 to 6/60. The minimum binocular horizontal field requirement ranges from 110° to 150°. In general, standards for a commercial licence are stricter compared to a private licence. A literature review could not support the current driving standards as evidence‐based. Conclusions and Relevance: The disunity of driving vision requirements worldwide likely reflects the inconclusive evidence base. Accounting for individual differences and the ability to predict individual risk is important in the context of determining driving licensure.